RoboVR: A Digital Twin Based Framework for Low-Cost 4DoF Robotic Arm Control - Wiriasto, Giri Wahyu; Sendari, Siti; Lestari, Dyah; Iqbal, Muhamad Syamsu; Mochtar, Norrima (Universitas Ahmad Dahlan, 2025)
The growing need for remote operation in risky situations has encouraged the use of robots that can be controlled from virtual environments. Integrating digital twin and virtual reality offers a way to monitor and control physical systems in three dimensional space. However, many existing implementations still depend on expensive robotic hardware and closed-loop control, while digital twin and virtual reality in open-loop mode is rarely reported and still faces the lack of feedback and the risk of mismatch between virtual motion and physical motion.This study proposes an experimental digital twin and virtual reality framework built on lightweight hardware to control a 4-DoF robotic arm using Arduino and PCA9685, with Unity acting both as the digital twin environment and as the source of kinematic commands. Method covers integration design, calibration of Unity angle to PWM mapping, execution on servos, and preparation of data to compare virtual joint angles with measured servo angles. Testing and validation were carried out through stepwise rotation of the ‘Base’, ‘Shoulder’, ‘Elbow’, and ‘End-effector’ joints to evaluate how well the physical motion followed the virtual model. Results show that the right and left ‘Base’ joints achieved small mean errors of -1.60 and 1.8 degrees, with variance of 1.35 and 1.62. The ‘Elbow-down’ motion was also accurate with a mean error of 1.43 degrees and a variance of 0.98. The largest deviation occurred in the ‘Shoulder’ joint, at -10.67 and 26.5 degrees. These findings confirm that open-loop digital twin and virtual reality control is feasible for low-cost platforms.